DOI: 10.18297/etd/3058
|View full text |Cite
|
Sign up to set email alerts
|

Binder jetting additive manufacturing process fundamentals and the resultant influences on part quality.

Abstract: for the scientific conversations and insightful suggestions about my research as well as the tremendous help for conducting different experimentations. I am truly thankful to all my friends and colleagues for their support and friendship. I also acknowledge the kind assistance and contributions of the staff of the Rapid Prototyping Center (RPC) at University of Louisville. Last but not least, I would like to thank my parents whose love and guidance are with me in whatever I pursue; and my best-friend loving wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 158 publications
(384 reference statements)
1
31
0
Order By: Relevance
“…The plots of the surface roughness found with the Keyence microscope can be seen in Figures 7 and 8. The surface roughness values are also in agreement with literature values of sintered parts with similar particle size distributions [9,13]. A topology map of the 10 pL sample printed at 0 degrees and 3 mm/sec taken with the Keyence microscope at 100x magnification can be seen in Figure 9.…”
Section: Resultssupporting
confidence: 88%
“…The plots of the surface roughness found with the Keyence microscope can be seen in Figures 7 and 8. The surface roughness values are also in agreement with literature values of sintered parts with similar particle size distributions [9,13]. A topology map of the 10 pL sample printed at 0 degrees and 3 mm/sec taken with the Keyence microscope at 100x magnification can be seen in Figure 9.…”
Section: Resultssupporting
confidence: 88%
“…Process ends with drainage and a decreasing drawing area (DDA). This model neglects the dynamics of the drop impact but shows the interaction of a sitting drop on a powder bed 10,26,27 The capillary pressure is the driving force for spreading and infiltration can be calculated by the Young-Laplace equation:…”
Section: Powder-binder Interactionmentioning
confidence: 99%
“…Through the manufacturing experiments, a total of ten rectangular prism-shaped samples (18 × 14.5 × 6 mm 3 ) were printed for the microstructural analysis and mechanical testing. We observed that the geometry of the part has no influence on the density of the green parts 30,31 . The rectangular prism shape for BJP samples were selected for further characterization.…”
Section: Methodsmentioning
confidence: 66%
“…Z d is the current building height. From ( 2 ), a direct relation between the layer thickness and the binder saturation is evident and this is the reason behind "green" body’s mechanical properties and dimensional accuracy 31 .…”
Section: Methodsmentioning
confidence: 99%